Results of Using Various Conduction System Pacing Options in Patients with Bradyarrhythmia - Perepeka, Eugene O.; Kravchuk, Borys B. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Chronic right ventricular myocardial pacing causes an asynchronous pattern of left ventricular activation, reduces left ventricular ejection fraction (LVEF), and may be associated with worsening of clinical outcomes in the long term. Although with the emergence of algorithms that minimize ventricular pacing it became possible to reduce the percentage of paced complexes in patients with sinus node dysfunction, permanent ventricular pacing is still inevitable in patients with high-degree atrioventricular (AV) block. The use of permanent conduction system pacing is a promising method for preserving the physiological activation of the ventricular myocardium and preventing the development of heart failure due to ventricular dyssynchrony. The aim. To analyze the immediate and long-term results of the use of conduction system pacing in patients with indications for permanent ventricular pacing. Materials and methods. This study included 18 patients with indications for permanentventricular pacing who were operated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine in the period from 01/01/2013 to 12/31/2022, in whom permanent conduction system pacing was used. There were 17 patients with bradyarrhythmias, of these 16 (88%) suffered from high-degree AV block (including 1 patient with Frederick’s syndrome and 1 (5%) patient with atrial ϐibrillation with slow ventricular response) and 1 (5%) patient with ischemic cardiomyopathy with left bundle branch block and ϐirstdegree AV block with indications for cardiac resynchronization therapy. The mean age of the patients was 55 ± 16 years (8 men, 10 women), LVEF at the time of the intervention was 56.42 ± 9.13 %, end diastolic volume 130.2 ± 23.8 ml, end systolic volume 55.1 ± 17.7 ml, diameter of the left atrium 4.01 ± 0.6 cm. The average QRS width before implantation was 116.5 ± 27.7 ms. In 6 (33%) patients, a special delivery system (С304-L69, Medtronic in 1 patient [5%], C315HIS in 5 [27%] patients) and 4.1F active ϐixation lead Medtronic 3830 Select Secure (69 or 74 cm) were used; in other cases (66%) standard 6F leads with active ϐixation and a lumen for a stylet without a delivery system were used. Results. The average follow-up period after implantation of pacemaker was 36.35 ± 29.65 months. During the observation period, LVEF was 57.07 ± 5.38 %, end diastolic volume111.5 ± 18.09 ml, end systolic volume 49.5 ± 13.4 ml, diameter of the left ventricle 3.9 ± 0.5 cm. The mean duration of paced QRS was 119.1 ± 10.09 ms. In 6 patients (33%), it was possible to demonstrate a change in the QRS width when the amplitude of ventricular stimulation was reduced, with 2 variants of transitions: 1) 4 (22%) patients with a transition from non-selective His bundle pacing (NSHBP) to selective His bundle pacing (SHBP), in 2 (11%) of these patients with a transition from SHBP with correction of right bundle branch block (RBBB) to SHBP without correction of RBBB, and then loss of capture of the myocardium of the ventricles; 2) 2 patients (11%) with a transition from NSHBP to myocardial septal ventricular pacing and further with a decrease in amplitude to the loss of capture of the myocardium of the ventricles. One (5%) patient with complete heart block had permanent non-selective left bundle branch area pacing. The other 11 (61%) patients met the criteria for parahisian pacing without visible transitions with a change in the amplitude of ventricular pacing. The average global longitudinal strain was -17.6 ± 2.7 %. The average interval from the stimulus to the peak of the R-wave in lead V6, which indicated the time of left ventricular activation, was 73.2 ± 8.7 ms. Pacing parameters were standardly set according to the primary indications, but with correction of the amplitude of ventricular stimulation relative to the thresholds of pacing of the conduction system. AV delay was corrected for the latency from the stimulus to the onset of the QRS in SHBP or for the duration of the “pseudodelta” wave in NSHBP which in both cases was the duration of the H-V interval. There were no complications in the acute or long-term postoperative period. Conclusions. Conduction system pacing is a challenge in the practice of cardiologist for treating life-threatening bradyarrhythmias and heart failure, but at the same time it is a safe method that provides physiological electrical and mechanical activation of the myocardium of the ventricles, that allows to effectively avoid the consequences of dyssynchrony due to permanent myocardial ventricular pacing.